2017
DOI: 10.1080/15205436.2017.1291817
|View full text |Cite
|
Sign up to set email alerts
|

The Appeal of Media Populism: The Media Preferences of Citizens with Populist Attitudes

Abstract: Although a growing body of literature points to the particular media diet of populist voters, we know too little about what specific media preferences characterize citizens with populist attitudes. This article investigates to what extent citizens with antiestablishment and exclusionist populist attitudes are attracted to attitudinalcongruent media content. We collected survey data using a nationally representative sample (N = 809) and found that citizens' preferences for media content are in sync with their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 40 publications
0
73
0
2
Order By: Relevance
“…Often referred to as the study of "populist attitudes," this research starts from the assumption that populist ideas must resonate with the public to be influential (Hawkins and Rovira Kaltwasser 2018;Spruyt, Keppens, and van Droogenbroeck 2016). Therefore, scholars examine how populist discourses, styles, and strategies among political elites correspond with the distribution of populist ideas among ordinary citizens (e.g., Castanho Silva et al 2018;Hameleers, Bos, and Vreese 2017;Hawkins, Riding, and Mudde 2012;Hieda, Zenkyo, and Nishikawa 2019;Schulz et al 2018;Spruyt, Keppens, and van Droogenbroeck 2016). The promise of this line of research is that understanding populism at the individual level may help understanding populism at the societal level, thus promoting the comprehension of how the "Populist Zeitgeist" (Mudde 2004) affects health and outlook of pluralist democracies.…”
Section: Introductionmentioning
confidence: 99%
“…Often referred to as the study of "populist attitudes," this research starts from the assumption that populist ideas must resonate with the public to be influential (Hawkins and Rovira Kaltwasser 2018;Spruyt, Keppens, and van Droogenbroeck 2016). Therefore, scholars examine how populist discourses, styles, and strategies among political elites correspond with the distribution of populist ideas among ordinary citizens (e.g., Castanho Silva et al 2018;Hameleers, Bos, and Vreese 2017;Hawkins, Riding, and Mudde 2012;Hieda, Zenkyo, and Nishikawa 2019;Schulz et al 2018;Spruyt, Keppens, and van Droogenbroeck 2016). The promise of this line of research is that understanding populism at the individual level may help understanding populism at the societal level, thus promoting the comprehension of how the "Populist Zeitgeist" (Mudde 2004) affects health and outlook of pluralist democracies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Chile voters of leftist parties showed stronger POLARIZING NEWS EFFECTS ON POPULIST ATTITUDES populist attitudes than those of other parties, which is a plausible finding in the context of South America (Hawkins & Kaltwasser, 2014). Moreover, recent research has demonstrated that populist attitudes are related to a preference for populist media messages (Hameleers, Bos, & de Vreese, 2017) and to the perception of hostile mainstream media . These findings suggest that there will also be media effects on populist attitudes.…”
Section: Populist Attitudes In the Publicmentioning
confidence: 99%
“…Taken together, the evidence suggests that populist radical right parties, their messages, and the topics for which they hold issue-ownership are likely to be dominant and highly visible on social media platforms, also to citizens who are not directly connected with PRRPs on social media and who do not search for the content, that is, those who are incidentally exposed to the news (see Bode, 2016;Fletcher & Nielsen, 2017;Kim, Chen, & Gil de Zúñiga, 2013). Previous research has shown that exposure to such messages can enhance exclusionist attitudes and endorsement for populist radical right parties (Hameleers, Bos, & de Vreese, 2018;2017a;2017b). For example, being confronted with information that attributed blame for negative developments in the Dutch labour market to the national government or the European Union increased the propensity to vote for the Dutch PRRP Partij voor de Vrijheid (Hameleers et al, 2018).…”
Section: The Affinity Between Social Media and Populist Radical Rightmentioning
confidence: 99%